Dielectric and microstructural properties of BaTiO3 and Ba0.9925Er0.0075TiO3 ceramics - Ismail Fatin Adila; Maulat Osman Rozana Aina; Idris Mohd Sobri; Taking Sanna; Zahid Jamal Zul Azhar (EPJ Web of Conferences, 2017)
BaTiO3 and Ba0.9925Er0.0075TiO3 ceramics were investigated regarding their dielectric and microstructure properties via conventional solid state reaction method. The phase pure samples were obtained when heated at 1400°C for overnight. The effect of Er3+ doped into BaTiO3 on dielectric properties and microstructural properties was investigated for composition of BaTiO3 and Ba0.9925Er0.0075TiO3. The analysis was made by X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and Impedance Analyzer. The XRD patterns of BaTiO3 and Ba0.9925Er0.0075TiO3 are phase pure and identical with tetragonal perovskite structure with space group of P4mm. The lattice parameters and unit cell volume of BaTiO3 increased by doping with Erbium as the crystallite size decreased. Measurements of dielectric properties were carried out as a function of temperature up to 200°C at different frequencies. Ba0.9925Er0.0075TiO3 exhibit the high value of dielectric constant (ε=6179) at Curie temperature (TC) of 120°C. SEM analysis of BaTiO3 and Ba0.9925Er0.0075TiO3 ceramics showed that the grain sizes of BaTiO3 and Ba0.9925Er0.0075TiO3 were ranged from 3.3µm-7.8µm and 2.2µm-4.7µm respectively.